Effect of ulcerative colitis and smoking on rectal blood flow. Issue 9 (September 1990) - Srivastava, E D; Russell, M A; Feyerabend, C; Rhodes, J
Abstract : Rectal blood flow was measured by laser doppler flowmetry over 60 minutes in eight patients with colitis in remission and eight healthy male non-smokers. Ten smokers were also examined on two occasions, one of which included smoking a cigarette. Plasma nicotine concentrations were measured in smokers. All subjects showed a pronounced fall in rectal blood flow in the first 30 minutes and patients with colitis had significantly higher values compared with smokers (p less than 0.002; p less than 0.04) and non-smokers (p less than 0.007; p less than 0.002) during the first and second 30 minutes respectively. Values in smokers and non-smokers were similar, but smoking a cigarette was associated with a significant fall in blood flow (p less than 0.04) and this change was inversely related to the rise in plasma nicotine concentration (r = -0.63; p less than 0.05). The findings may be relevant to the association between colitis and the smoking history.